Cimetidine Pharmacodynamics and Pharmacokinetics in Healthy Subjects: A Comparison of Tablets and Suspension - ABR Thomson; P Kirdeikis; L Zuk; RE Samuels; P Zarevics (Canadian Journal of Gastroenterology)
The objective of this study was to compare the effect of cimetidine 200 mg tablet with that of cimetidine suspension (200 mg/10 mL), a 20 mL suspension of 800 mg magnesium hydroxide and 912 mg aluminum hydroxide, and matching placebo on intragastric pH of healthy volunteers. There were 13 males and seven females, mean age 23 years (range 20 to 32) and mean weight 72 kg (range 55 to 89). The intragastric pH of each subject was measured over 6 h starting immediately before dosing on each of five study days. Cimetidine plasma levels were measured for 6 h after dosing on each of the cimetidine study days. Cimetidine tablet and suspension were superior to placebo tablet or suspension or to the magnesium hydroxide/aluminum hydroxide suspension in the area under the pH time curve from 0 to 6 h, percentage time pH of at least 3.5, change from pretreatment pH area under the pH time curve (0 to 6 h) and maximum increase in pH. Mean plasma cimetidine levels were significantly and positively correlated to mean intragastric pH for both cimetidine tablets and cimetidine suspension. Comparing cimetidine concentration (Cmax) and lower percentage time plasma cimetidine concentration was at least 0.5 μg/mL (the minimum therapeutic level). These pharmacokinetic variations between cimetidine suspension and tablets may have partially explained the pharmacodynamic differences of the lower area under the pH time curve (0 to 6 h). The results indicate that both cimetidine tablets and cimetidine suspension significantly increase intragastric pH relative to the magnesium hydroxide/aluminum hydroxide suspension, placebo tablets or placebo suspension. Based on the assumption that elevation of intragastric pH is an important factor for alleviation of the symptoms and for the healing of peptic disorders, the results of this study suggest that both cimetidine tablets and cimetidine suspension should be effective treatment.